(untitled) (Numerus academy review, 2026)
This work is an attempt to analyse the final secondary exam (BAC) in terms of its response and compliance with the educational, pedagogical and didactical requirements of the method being applied in the Algerian school. Competency-Based Approach (CBA) has been carefully selected and applied to meet the policy maker’s ends. Questionnaires are the main tool for data collection, in addition to the comparative analysis used to critically compare two exam samples belonging to different Algerian educational periods in order to find out the differences and similarities that might be between them. The research shows that teachers of English find the exam incomplete since it does not consider testing oral competency. Moreover, there is a very slight difference found between the two exam samples although they had been designed on the grounds of two different methods to EFL teaching. An overlap is apparently characterising the learning outcomes of CBA with the final official exam (BAC) objectives in Algeria.